Islamic Study of Parents' Perceptions and Efforts to Overcome the Tradition of Smoking Freedom for Elementary School Age Children on Eid Al-Fitr - Ikbal, Muhammad; Rahmadani, Siska (JASNA : Journal For Aswaja Studies, 2024)
Smoking is a problem that is still very difficult to solve, because smoking is a very common and widespread habit in society. Then a unique habit was discovered in Batu Madingding Village, Batang Natal District, Mandailing Natal Regency, that elementary school children aged 10-12 years were given the freedom to smoke on Eid al-Fitr. The aim of this research is to determine parents' perceptions of the tradition of freedom of smoking for elementary school -aged children on the Eid al-Fitr holiday. The method used in this research is a qualitative descriptive method. The data collection technique used was observation and interviews . To ensure the validity of the data in this research, triangulation was used. Then analyzed using the Miles and Huberman model. Parents' perception of the tradition of freedom of smoking for elementary school age children on Eid al-Fitr is following the traditions that apply in society, giving children pleasure, buying cigarettes. Efforts made by parents to prevent children from smoking are by forbidding children to smoke, giving advice to children, and not buying children cigarettes.